The Influence of Islam on International Law: What is at Stake? - Gollubovic, Dragan M (Poslovna ekonomija, 2018)
This article sets out to examine the overall influence of Islam on International Law (also referred to as Public International Law or the Law of Nations). More specifically, it provides a critical overview of sources and rules governing conduct of war and peace in Islam, and its arguably positive influence on the development of International Law. This undertaking serves a broader purpose of discerning reasons as to why radical (miss) reading of Islam, which—in violation of International Law—calls for all out jihad against non-Muslims, has gained in popularity in the last several decades. Special attention in this respect is given to a lack of legitimacy of governments in the Middle East as a source of religious radicalization, as well as policy measures those governments need to put in place, in order for a more progressive understanding of Islam to prevail across the board. Key words: Islam, International Law, Jihad, Middle East, Political Legitimacy, Political Reforms